Poetree – A Poetic Inquiry into Interdisciplinary Learning Based on the Gaelic Tree Alphabet. Issue 3 (3rd July 2021) - Haggith, Mandy
ABSTRACT: The Gaelic tree alphabet is an ancient connection between trees and writing. In the Highlands of Scotland, it has recently been used as a structure for engaging people in interdisciplinary encounters at the boundary between forestry and literature, through a project called A-B-Tree. Poetic inquiry methods enabled exploration of how making a creative response to a tree can influence learning and attitudes. The A-B-Tree project has amassed evidence that tree-related wordplay is good for our well-being and stimulates and deepens thinking about trees. The poetic inquiry method has itself been a source of insights into the epistemological edge-zone between ways of knowing in poetry, folklore and forest ecology in particular and more generally between artistic practice and scientific knowledge.